Is innovation a second order construct: clarifying the formative and reflective measures of innovation - Arshi, Tahseen (Archives of Business Research, 2017)
The primary purpose of this study is to bring clarity to the measurement of innovation construct, particularly within corporate firms. Measures of innovation continue to be debated in academic literature and absence of universally accepted and valid quantitate scale of innovation can be attributed to lack of clarity of innovation measures. Academic research needs to increase the understanding of diverse conceptualization and operationalization of the innovation construct and its implications in research and practice. Drawing from corporate entrepreneurship and innovation literature, this study argues that innovation is a second order construct consisting of radical and incremental innovation degree and frequency, which are its reflective measures. It further argues that readiness for innovation is a formative measure and an antecedent to innovation. The study uses a dominantly quantitative approach and utilizes structural equation modelling to test the measures of innovation through first and second order measurement and structural models. The results of the study on a sample of Omani corporate firms indicate that measurement of innovation can better understood through both reflective and formative measures. Key Words: Corporate entrepreneurship, radical innovation, incremental innovation, formative and reflective measures.